A Hybrid Forward–Backward Algorithm and Its Optimization Application - Liya Liu (Mathematics, 2020)
In this paper, we study a hybrid forward−backward algorithm for sparse reconstruction. Our algorithm involves descent, splitting and inertial ideas. Under suitable conditions on the algorithm parameters, we establish a strong convergence solution theorem in the framework of Hilbert spaces. Numerical experiments are also provided to illustrate the application in the field of signal processing.